Design and Development of an Experimental Aeroelastic Test Rig - Mohd. Rafie, A. S.; Attaran, A.; Majid, D. L.; Basri, S. (2006)
Aeroelasticity has played an important role in the design and testing of almost every new flight vehicle. As such, wind tunnel tests in aeroelasticity are widely conducted to determine and understand the physics of aeroelastic phenomena such as flutter and divergence so that they could be taken into account during the design stage. This paper describes and presents the design and development of an aeroelastic test rig to be used in conjunction with the existing 1m by 1m low speed wind tunnel. The test rig comprises a frame, rotating disk, brake system, and universal clamp. The proposed test rig is designed for testing of cantilevered model, which can be as simple as a beam model to a more complicated scaled-down actual wing model subject to the existing wind tunnel constraints. The test rig will also have the ability to rotate the model at various angles of attack.